2018
DOI: 10.1016/j.jid.2018.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of IL-17C Reduces Skin Inflammation in Mouse Models of Psoriasis and Atopic Dermatitis

Abstract: IL-17C is a functionally distinct member of the IL-17 family that was believed to play a role in the pathogenesis of psoriasis. Here we confirmed that IL-17C is involved in psoriasis and explored potential roles for IL-17C in atopic dermatitis (AD). An anti-IL-17C antibody, MOR106, was generated that potently and selectively binds to human and mouse IL-17C, thereby inhibiting the binding of IL-17C to its IL-17RE receptor. The antibody inhibited cutaneous inflammation in an IL-23-induced psoriatic-like skin inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(111 citation statements)
references
References 26 publications
3
99
0
7
Order By: Relevance
“…Of note, IL‐17C induced chemokines of Th1 (CXCL10), Th2 (CCL5) and Th17 immunity (CXCL8), thus pointing out that IL‐17C is not exclusively related to one specific type of T cell‐mediated inflammation. Recently it was shown that depletion of IL‐17C signalling decreases inflammation in murine models of ISD . Based on the mechanistic data obtained in our cell culture experiments, we could prove the pivotal role of IL‐17C for immune cell recruitment in these murine models as we demonstrate that blockade of IL‐17C resulted in significantly reduced T cell, neutrophil and eosinophil numbers.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Of note, IL‐17C induced chemokines of Th1 (CXCL10), Th2 (CCL5) and Th17 immunity (CXCL8), thus pointing out that IL‐17C is not exclusively related to one specific type of T cell‐mediated inflammation. Recently it was shown that depletion of IL‐17C signalling decreases inflammation in murine models of ISD . Based on the mechanistic data obtained in our cell culture experiments, we could prove the pivotal role of IL‐17C for immune cell recruitment in these murine models as we demonstrate that blockade of IL‐17C resulted in significantly reduced T cell, neutrophil and eosinophil numbers.…”
Section: Discussionsupporting
confidence: 64%
“…MOR106 is a novel, fully‐human anti‐IL‐17C IgG1 antibody, which selectively inhibits the binding of IL‐17C to the IL‐17RA/IL‐17RE receptor heterodimer in humans and mice. Recently, it was shown that MOR106 attenuates skin inflammation in murine models of AE and psoriasis in terms of epidermal thickness and cytokine expression in the skin . However, it remained elusive how IL‐17C depletion affects immune cell composition in these models.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is characterized by complex interactions between environmental and genetic factors, including a skin barrier defect, Th2 inflammation with elevated serum IgE and eosinophilia . Classically, AD is associated with the Th1/ Th2 immune response; however, there is growing evidence that Th17 and Th22 inflammatory responses are also involved . One of the most well‐known risk factors for AD is a mutation of filaggrin (Flg) gene which is important for skin barrier .…”
Section: Introductionmentioning
confidence: 99%